IMPROVING STUDENTS’ VOCABULARY ON DESCRIPTIVE TEXT BY USING MIME GAME (A STUDY CONDUCTED AT SMP NEGERI 2 TOMPASO) - Marisa Nikita Kolopita; Sanerita T. Olii; Rinny Rorimpandey (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this research is to find out whether or not using Mime Game can improve students’ vocabulary mastery on descriptive text. The subjects of this research were one class of the seventh grade that consisted of 36 students at SMP Negeri 2 Tompaso. This was quantitative research of pre-test and post-test with pre-experimental design. The data pre-test and post-test were collected using a 50 item Fill-in-the-blank test. The results of this research indicate that there was a significant difference between the pre-test and post-test. The results of mean score showed improvement between the pre-test (42.7) and the post-test (85.05), with the post-test score higher than the pre-test. Therefore, it can be said that the use of the Mime Game was effective in improving students' vocabulary. English teacher should teach Vocabulary by using mime games with descriptive text by using simple English' and not always using monotonous text or handbook to help students remember words more easily